Self-sustained movement of condensate drop on uniform temperature surface during Marangoni dropwise condensation. (October 2019) - Chen, Zhihao; Fan, Yaru; Utaka, Yoshio; Zhao, Yanjie
Highlights: Self-sustained movement of condensate drops was studied in Marangoni condensation. Two different modes of drop behavior on uniform temperature surface were clarified. Two modes were drops of sustained moving and stagnant depending on initial velocity. Abstract: During the condensation of some binary vapor mixtures so-called 'positive system', in which the more volatile component has the higher surface tension (e.g., water–ethanol), Marangoni dropwise condensation occurs owing to the temperature-induced local concentration and surface tension instability. It was found that the spontaneous movement of condensate drops occurred from the low- to high-temperature side of the heat transfer surface due to the concentration and surface tension difference around the drops, which are induced by the bulk temperature gradient. In this study, it was newly discovered that the spontaneous movement of condensate drops could be 'self-sustained' even without the presence of a bulk temperature gradient on the heat transfer surface. By applying the neighboring temperature gradient region and uniform temperature region on the condensing surface, two different modes of drop behaviors were observed during the experiments: (1) For the condensate drops with notable initial velocities in the temperature gradient region, the spontaneous movement was sustained in the uniform temperature region; (2) for the condensate drops initially formed in the uniform temperature region, the spontaneous movement did not occur owing to the lack of initial velocity. The reason for self-sustained movement of condensate drops can thus be inferred to be the presence of a self-formed temperature gradient around the moving condensate drops.